Superstruktur Wacana Fashion Dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia Di Sekolah Menengah Pertama - Devy, Shinta Kharisna; , Drs. Agus Budi Wahyudi, M.Hum (2016)
This research has three objectives. 1. Expose the structure of discourse in fashion magazines and tabloids. 2. Expose the schema order of discourse in fashion magazines and tabloids. 3. Expose the implementation of research results superstructure discourse fashion as Indonesian Language learning materials in junior high school. This type of research including qualitative descriptive. The data in this study of text intact. As for the source of the data in this study was the Femina magazine, a Tabloid Daily, and the Fashionable Public Solopos, Sindo. Data collection techniques in this research using the techniques of documentation. Data analysis using the equal method, equal referential is indeterminate in the form of the referring tool. The results of the research there are three things. 1) discourse of fashion in magazines and tabloids have different structures, based on the genre of discourse. 2) Scheme and the order of discourse is based on the text type, there are Description and Exposition, description text has two elements there are general description and description sections, that the text of the exposition has three elements, there are the opening section, content section, and closing section. Description of the general discourse fashion found in first paragraph, the other is a description of the part. In this research there are also three data that does not have a general description, all the paragraph is description of the part. In the opening section of exposition text outline is located at the beginning of the paragraph, the closing section is placed at the end of the paragraph. The share of the most populated part of contents discourse. There are two discourses that don't have the opening section, as well as 4 discourse has no closing section. Part of the opening and closing is not an absolute thing in discourse. 3) implementation of the results of this research can be used as teaching material in junior high school about recognizing, understanding the structure of the text description and Exposition. The text used as learning materials is text that has a complete structure. Keywords: implementation, Superstructure, the discourse of fashion.